[OP.7D.04] NOCTURNAL HYPERTENSION AND PROGRESSIVE RENAL FUNCTION LOSS IN RENAL TRANSPLANT PATIENTS. (September 2017) - Mallamaci, F.; D'Arrigo, G.; Tripepi, R.; Leonardis, D.; Porto, G.; Testa, A.; Elhafeez, S. Abd; Mafrica, A.; Versace, M.C.; Provenzano, F.; Tripepi, G.; Zoccali, C.
Abstract : Objective: Hypertension is considered as a long-term, non-immunological risk factor for renal function loss in kidney transplant patients. However, there are no longitudinal studies focusing on the relationship between golden standard BP measurements (24 h ambulatory BP) and the GFR evolution over time in renal transplant patients. Design and method: In a cohort of 260 renal transplant patients we investigated the relationship between the main components of the 24 h ABPM profile (day-time and night time average BP) with the evolution of the GFR over time (by the linear mixed model, LMM) and with the time to a combined end point (>30% GFR reduction, dialysis/transplantation and death) by Cox's regression analysis. On average, 48 longitudinal eGFR measurements were available and 211 patients (81%) had more than 20 measurements over a follow up period ranging from 2 days to 12 years. The predictive values of non-nested models including an identical set of standard risk factors and each BP component were assessed by the −2 LL statistics. Results: In the analysis by the LMM adjusting for a large series of potential confounders (baseline GFR, gender, age, BMI, diabetes, smoking, 24 h urinary protein, cholesterol, hemoglobin, albumin, phosphate and the immunosuppressive drug combinations) both day time and night time BP were significantly related to longitudinal eGFR measurements (P < 0.01) but the LMM-based on night time BP provided a better data fit (by −2 LL statistics) than that based on day time BP. During the follow-up period, 123 patients experienced the combined end point, and the model based on night time BP provided the best data-fit for predicting the outcome. Conclusions: Ambulatory BP measurements coherently predict the risk of GFR loss over time and the risk of developing a combined renal end-point. Night time BP is a stronger indicator of the risk of progression of renal disease than day time BP. These findings optimization of BP control may slow the rate of GFR loss in renal transplant patients and suggest that interventions targeting night time BP may afford renoprotection superior to that of day time BP.